On being nonreligious in contemporary Japan: decline, antipathy, and aversion to institutions - Reader, Ian (Bloomsbury Academic, 2025)
"This book challenges the notion of the nonreligious in Japan being religious through tradition and institution. Ian and Clark instead argue that many Japanese say they are nonreligious because they actually dislike religion and want to distance themselves from it. To support this argument, the book explores how religion is in decline in Japan today. Demonstrating how negative images of religion are produced in the mainstream media, in popular culture, and by various groups and people, this book also explores specific case studies such as anti-cult organizations, lawyers, government agencies, intellectuals, and religious organizations"--